Changes in body position on the bike during seated sprint cycling: Applications to bike fitting - Bini, R.; Daly, L.; Kingsley, M. (European Journal of Sport Science, 2020)
Dynamic bike fitting often includes the optimisation of lower limb joint kinematics while participants undertake sub-maximal intensity cycling; however, this practice might not be appropriate for sprint cycling. This study aimed to determine if trained cyclists maintain lower limb angles, defined during dynamic sub-maximal bike fitting, while completing seated sprint cycling. Fifteen competitive cyclists completed two testing sessions. Dynamic bike fitting was undertaken during the first session, where handlebar positions were identified to produce pre-determined hip flexion angles (70°-110°) during sub-maximal cycling using an inertial-based motion tracking system. In the second session, full body kinematics were determined during two 6-s sprints performed at each of the pre-determined handlebar positions. During sprinting, measured right hip angles were only different at 110°, when compared with 90° (p < 0.01, d = 0.95), and 80° (p < 0.01, d = 1.49). For the left leg, measured hip angles differed between 110° vs. 90° (p < 0.01, d = 1.52), 110° vs. 80° (p < 0.01, d = 2.09), and 100° vs. 80° (p = 0.04, d = 1.06). Even though changes in bike configuration resulted in 10° increments of hip flexion during dynamic sub-maximal bike fitting, these hip angles were not replicated during sprinting. Therefore, dynamic sub-maximal bike fitting leading to changes in handlebar positions that produce hip angles of 80°-100° might not influence cycling performance due to acute changes in the body position of cyclists on the bicycle during a sprint.